(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
The last few decades have witnessed unprecedented tourism growth, accompanied by the unstoppable growth of adverse effects, including the excessive number of visitors in tourist destinations, which have caused them to exceed their carrying capacity. The saturation of tourist destinations has led governments to adopt measures as soon as possible to safeguard the environment through a sustainability-oriented approach. As one of the most profitable sectors for governments, the tourism industry must be at the forefront of the global sustainability challenge. In this context, the circular economy, with its approach geared towards a gradual move away from linear-traditional resource management, seems to lend itself well to this. Indeed, tourism is a product of the linear model; nevertheless, it can be integrated into circular systems. This work aims to present what is meant by the circular economy, highlighting its main aspects and presenting the most relevant circularity issues in tourism. The authors’ primary purpose was to provide a review of the works conducted in the last years to clarify what has been discussed in the context of circular tourism. Consequently, a conceptual framework of the topics involved has been implemented to overview the circular economy and tourism-related issues. A particular focus on the business models of the circular economy, with a brief application to the tourism sector, is proposed. The results show the lack of contributions in the literature in terms of circular economy and circular tourism; finally, in the conclusions, the authors emphasize the importance of sustainability of tourism mobility